Analyzing the fraud awareness from UiTM Pahang's academic staff perspectives / Mohamad Ridhuan Mat Dangi and Noor Hasimah M. Yacob - Mat Dangi, Mohamad Ridhuan; M. Yacob, Noor Hasimah (2013)
There are many reported cases of fraud activities which bring devastating impacts in various losses including the downfall of the well established organization and business entity. It often involves the significant losses not only in terms of financial position, but also reduce the moral perception and might able to diminish the trust. Fraudulent activities are not a new issue in the area of corporate and organizational conduct in the world It is in fact, has evolved and expanded to come out with several schemes and techniques to conduct these activities with the numerous mediums and channels to perform this criminal behavior. The study by Donald R. Cressey in 1950 's about the embezzlers have developed the fraud triangle theory which outlined three characteristics that enabled fraud activities to occur in the organization (Capote, 2004). This study tends to investigate the level of knowledge, awareness and understanding of fraud activities. It is also purportedly to identify which elements of fraud triangle theory have the highest influence on fraud activities and examining the fraudsters profile from UiTM Pahang's academic staff perspective. Findings from this study show that most of the academic staffs of UiTM Pahang have a moderate knowledge and awareness about fraud and generally the information were obtained from the internet. Most of them chose opportunity as the motivational factor for someone to perpetrate fraud and it will impact the society as a serious problem. They also agreed that fraud perpetrator is male with the age in range of28 to 32 years, by having 6 to 10 years working experience as a senior management with the professional education level. It is believed that, this study will create the understanding and awareness about fraud activities and its behavior and will make people become more sensitive about the negative impact brought by fraud Thus, by explaining and promoting the perils of the fraud to all the individuals, it is crucial to ensure that the awareness of this misbehavior can be recognized at the infancy stage before it becomes worse and damages the organization and individual itself in total.